Prognostic significance of the Tpe/Qtc ratio in predicting major adverse cardiac events in acute STEMI patients - Evren Dal; Suna Eraybar (Scientific Reports)
Abstract To evaluate the prognostic value of the Tpe/QTc ratio on admission electrocardiograms in predicting major adverse cardiovascular events (MACE) in patients with acute ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous intervention. STEMI is closely associated with increased mortality and MACE, often indicated by electrocardiographic findings of repolarization abnormalities. These can reflect myocardial damage from ischemia and other pathological developments during patient follow-up. This study retrospectively analyzed patients presenting with characteristic symptoms of STEMI who underwent primary percutaneous coronary angiography. Tpe, QTc, and Tpe/QTc ratios were measured from admission ECGs and correlated with angiographic results, 90-day mortality rates, and MACE subcategories. The Tpe/QTc ratio predicts cerebral ischemic stroke and recurrent unstable angina within 90 days post-STEMI. Using a cutoff of 0.190 for the Tpe/QTc ratio, the method demonstrated a sensitivity of 83.3% and a specificity of 66.1% (AUC 0.743 ± 0.078). Additionally, a lower Tpe/QTc ratio was significantly associated with 90-day mortality, while a higher ratio was linked to recurrent unstable angina (p < 0.03). Variability in the Tpe interval and the Tpe/QTc ratio in acute STEMI cases provide critical prognostic information regarding patient outcomes and MACE risks. These insights can inform clinical decisions regarding follow-up and treatment strategies, including adjustments to anticoagulation and considerations for repeat angiography.